Rural-urban interdependence - Tacoli, Cecilia (International Food Policy Research Institute, 2000)
Urban food and nutrition security depends on strong links between urban and rural areas. But policymakers and urban planners often ignore this interdependence. There are two broad, often overlapping, categories of rural-urban linkages. Spatial" links refer to the movement of people, goods, money, and information between urban and rural areas. "Sectoral" links describe the interdependence between agriculture on the one hand and industry and services on the other. In the next two decades, three main issues related to rural-urban interdependence are likely to emerge: (1) changes in land use around urban centers, from farmland to residential or industrial use; (2) greater diversification of income sources in rural and urban areas, often involving people migrating or commuting between the countryside and urban centers; and (3) changes in the direction and composition of internal migration... Understanding the importance of rural linkages to urban livelihood, food, and nutrition security is critical if policies are to improve the lives of the urban poor, rather than making them even more difficult than they already are." -- from Text